THE ROLE OF THE LEMBAGA MUSYAWARAH KELURAHAN IN MAINTAINING TWO-WAY COMMUNICATION WITH THE COMMUNITY - Serlin Maharani; RR. Roosita Cindrakasih (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
This study was motivated by the phenomenon of low participation among residents of RT 03 RW 04, South Utan Kayu Village, Matraman Subdistrict, East Jakarta, in conveying their concerns to the Village Consultative Body (LMK), despite the availability of communication channels. This study aims to determine the role of the LMK in maintaining two way communication with the community, to understand the forms of two way communication that occur, and to identify the obstacles encountered. This study employs the Symmetrical Two Way Communication theory proposed by Grunig and Hunt. The research method used is descriptive qualitative, with data collection techniques including non participant observation, in depth interviews, and documentation from five informants. The results indicate that the LMK serves as a communication bridge between residents and the village administration through deliberative forums and a WhatsApp group. The barriers identified include delays in following up on residents concerns due to bureaucratic processes, as well as limited resident attendance at deliberative forums. Thus, two way communication between the LMK and the community of RT 03 RW 04 South Utan Kayu continues despite various obstacles, as the LMK consistently fulfills its role as a conduit for residents concerns and information from the sub district office.